Outcomes in older kidney recipients from older donors: A propensity score analysis - Cuadrado-Payán, Elena; Montagud-Marrahi, Enrique; Casals-Urquiza, Joaquim; del Risco-Zevallos, Jimena; Rodríguez-Espinosa, Diana; Cacho, Judit; Arana, Carolt; Cucchiari, David; Ventura-Aguiar, Pedro; Revuelta, Ignacio; Piñeiro, Gaston J.; Esforzado, Nuria; et al. (Frontiers in Nephrology, 2022)
Background: the age of patients referred for kidney transplantation has increased progressively. However, the precise influence of age on transplant outcomes is controversial. Methods: retrospective study in which graft and recipient survival were assessed in a cohort of ≥75 years old kidney recipients and compared with a contemporary younger one aged 60-65 years through a propensity score analysis. Results: we included 106 recipients between 60-65 and 57 patients of ≥75 years old with a median follow-up of 31 [13-54] months. Unadjusted one- and five-year recipient survival did not significantly differ between the older (91% and 74%) and the younger group (95% and 82%, P=0.06). In the IPTW weighted Cox regression analysis, recipient age was not associated with an increased risk of death (HR 1.88 95%CI [0.81-4.37], P=0.14). Unadjusted one- and five-year death-censored graft survival did not significantly differ between both groups (96% and 83% for the older and 99% and 89% for the younger group, respectively, P=0.08). After IPTW weighted Cox Regression analysis, recipient age ≥75 years was no associated with an increased risk of graft loss (HR 1.95, 95%CI [0.65-5.82], P=0.23). Conclusions: these results suggest that recipient age should not be considered itself as an absolute contraindication for kidney transplant